From knowledge building to intercultural development of American mobile students in Spain - Méndez García, María del Carmen (Onomázein, 2020)
This paper looks into the intercultural development of a cohort of 26 American students in Spain. Spain constitutes the third preferred world destination of American sojourners. Starting from an analysis of students’ knowledge areas about the host culture, this study explores the relationship between intercultural knowledge and other dimensions of intercultural competence through students’ journals. Results indicate that sojourners increase their knowledge of 13 areas of the host culture, especially of issues related to food and drink, daily life, house, and institutions and services. Data also reveals that the acquisition of and reflection on culture-specific knowledge instigates intercultural development by honing awareness of intercultural verbal and non-verbal communication and the processes inherent in adjustment to life in the host country, learning from experience, and critical stances. The paper concludes that informed and critical reflection on sojourners’ experiences of otherness during study abroad, facilitated by an intercultural orientation program, favors positive attitudes towards the outgroup and enhances the intercultural attitudes of empathy, curiosity or willingness to adjust, along with the intercultural skills of communicative awareness, cultural awareness, awareness of the self and the other, action-taking, or suspending judgement